Avaliação da satisfação e impacto do trabalho em profissionais de saúde mental de um centro de atenção psicossocial - Santos, Alessandra Tais dos (2021)
Taking into account the scenario where cases of mental illness and the impact they cause are increasing and taking global proportions, it is necessary to emphasize the importance of the participation of health professionals in mental health services. It is known that, due to various factors, they may feel dissatisfied and overloaded in their services, which can cause damage in various aspects of their own lives, and somehow interfere in their working capacity and, indirectly, in the treatment offered to users of this system. Thus, the objective was to evaluate the satisfaction and service overload of professionals working in a CAPS in northern Mato Grosso. This is a cross-sectional observational study. first, the medical records of the unit were analyzed for respectful knowledge of the users whom the professionals have contact with. And for the analysis of satisfaction and burden, two scales were used, the Mental Health Service Burden Assessment Scale (IMPACTO-BR) and the Mental Health Service Satisfaction Assessment Scale (SATIS-BR). Descriptive and statistical analysis of the data was performed. The CAPS currently serves about 992 patients, most of them women and depression is the most prevalent pathology. The team is formed by 18 professionals, mostly women, with complete higher education, aged between 38 and 56 years. The application of the Satisfaction Scale showed individual scores ranging between 1.88 and 4.64 and an average score of 3.53, which is between the “indifferent” and “satisfied” categories. The average burden score was 1.51, indicating the degree of burden between the categories “not at all” and “not much”. The statistical analysis showed a significant difference in the comparison between the factors "Quality of Service" and "Working Conditions" of satisfaction in the Satis-BR scale, suggesting greater satisfaction of professionals with the quality of service. In addition, this study observed a positive influence of time on the factors “relationship at work” of the satisfaction scale and the “Effects on work” of the overload scale. It is concluded that the Mental Health professionals of the evaluated service, in general, do not feel overloaded or dissatisfied with the service. However, analyzing each subscale individually, professionals feel more satisfied in relation to factors related to the quality of the service offered than factors related to working conditions. It was also observed that the longer professionals work in the area, the more satisfied they are in relation to the relationship with the team and co-workers, and the less burdened they feel in relation to the effects that work has on their lives.